Характер соціальної комунікації в мережі інтернет - Девтеров, І. В. (НТУ "ХПІ", 2011)
The article examines the peculiarities of social communication in the Internet, specific of mass communication as well as draws attention to the importance of information in the net interaction.
Keywords: комунікація; інформація; комуніканта; реципієнт; інфовзаємодія